G protein alpha subunit multigene family in the Japanese puffer fish Fugu rubripes: PCR from a compact vertebrate genome. - Sarwal, M M; Sontag, J M; Hoang, L; Brenner, S; Wilkie, T M

(untitled) (Genome Research, 1996)
We compare the complexity and organization of the G protein alpha subunit multigene family in the vertebrate genomes of mammals and the Japanese puffer fish Fugu rubripes. Fourteen Fugu G alpha genes were identified of the 16 genes characterized previously in mammals, including Fugu genes from the four classes of alpha subunits Gs, Gi, Gq, and G12. Fugu and mammalian G alpha coding sequences are highly homologous, and the intron/exon structure of the fish and mammalian orthologs is identical throughout the coding regions. A novel G alpha gene, G alpha p1, was also identified in Fugu rubripes and two other species of puffer fish. The complete sequence of Gnaz and the tandemly duplicated genes Gnai2 and Gnat1 were obtained from a Fugu genomic cosmid library. Introns in the puffer fish G alpha genes lacked repeat DNA sequences, other than simple sequence length repeats, and most introns were significantly shorter in Fugu than in mammalian orthologs. The compact genome of puffer fish provides a unique vertebrate model for characterizing multigene families and identifying novel genes directly from genomic DNA by PCR amplification with degenerate primers. The fact that Fugu encodes most, if not all, of the G protein alpha subunits identified in mammals strongly supports Fugu as a model organism for vertebrate genome research.